Education and Employment Status of Children and Adults with Thalassemia in North America - Pakbaz, Zahra (2010)
BACKGROUND: Advances in the management of thalassemia have resulted in increased life expectancy and new challenges. We conducted the first survey of education and employment status of people with thalassemia in North America. PROCEDURES: A total of 633 patients (349 adults and 284 school age children) enrolled in the Thalassemia Clinical Research Network (TCRN) registry in Canada and the US were included in the data analysis. Predictors considered for analysis were age, gender, race/ethnicity, site of treatment (Canada vs. United States), transfusion and chelation status, serum ferritin, and clinical complications. RESULTS: Seventy percent of adults were employed of which 67 percent reported working full-time. Sixty percent had a college degree and 14% had achieved some post college education. Eighty-two percent of school age children were at expected grade level. In a multivariate analysis for adults, Whites (OR=2.76, 95% CI: 1.50-5.06) were more likely to be employed compared to Asians. Higher education in adults was associated with older age (OR=1.67, 95% CI: 1.29-2.15), female gender (OR=2.08, 95% CI: 1.32-3.23) and absence of lung disease (OR=14.3, 95% CI: 2.04-100). Younger children (OR=5.7 for 10 year increments, 95% CI: 2.0 – 16.7) and Canadian patients (OR=5.6, 95% CI: 1.5-20) were more likely to be at the expected education level. Neither transfusion nor chelation was associated with lower employment or educational achievement. CONCLUSIONS: Individuals with thalassemia in North America can achieve higher education; however, full-time employment remains a problem. Transfusion and chelation do not affect employment or education status of this patient population.